Cambridge Key English Test 5 - Cambridge University Press (Fahasa, 2011)
Authentic examination papers from cambridge esol;Official preparation material for cambridge english: Key, also known as Key english Tests (Ket); Cambridge Key English Test 5 contains four complete KET past papers from Cambridge ESOL. These official papers provide candidates with an excellent opportunity to familiarise themselves with the content and format of the KET examination and to practise examination techniques. The book contains practice material for Paper 1 (Reading and Writing) and Paper 2 (Listening), along with attractive colour visual material for Paper 3, which enables students to prepare thoroughly for the paired Speaking test. The audio CD set contains the recordings for Paper 2 (Listening). Cambridge University Press is the only official publisher of past papers from Cambridge ESOL